Analytical and numerical evaluation of the relationship between elongation calibration function and cyber standard tensile tests for ductile materials - N.Y. Kim; N.H. Kim; M.K. Razali; H.M. Lee; M.S. Joun (Materials & Design)
Cylindrical tensile testing is critically reviewed focusing on the gage length per diameter (GLPD) and its effect on the elongation. Flow behaviors and patterns of representative cold forging materials of SCM435, SWCH45F, S25C, SWCH10A, SUS304, A6061, and ESW105 are revealed focusing on accurately predicting their tensile tests with various GLPDs using the combined elastoplastic FEM and tensile test method (EP_CFTM). A GLPD-elongation curve, called numerical elongation calibration curve, is numerically constructed, revealing that the elongation of ESW105 changes around 22.1% when the GLPD changes from 3.98 to 5. A concept of cyber standard tensile test (CSTT) of the numerical specimen with a fixed GLPD of five, based on finite element method (FEM) with accurate flow functions, is proposed to improve the objectivity of tensile testing of circular specimens. The CSTT removes the effect of the gage length of the cylindrical tensile test on the tensile testing results. A novel analytical elongation calibration function is presented and numerically validated. This function simply maps an experimental tensile test to the analytical tensile test of the specimen with arbitrary GLPD.